Evaluation of the quality of artisanal Serrano and Colonial cheeses produced in São Francisco de Paula, RS - Lisiane da Silveira Garcia; Jéssica Aneris Folchini; Anelise Trindade Ramos; Andréa Karoline Mascitti; Renata Rebesquini; Thaís Oliveira Deon; Joana Gerent Voges; Danilo Cavalcante Gomes; Elisa Cristina Modesto (Revista do Instituto de Latícinios Cândido Tostes, 2022)
The differences between artisanal Serrano cheese (ASC) and Colonial cheese (CC) are related to the manufacturing method and mainly to the available legislation. This study aimed to evaluate the quality of Serrano and Colonial artisanal cheeses, made with pasteurized or raw milk, and ripened for 15 days, produced in the city of São Francisco de Paula, in Rio Grande do Sul. Information on animal handling and Good Milking Practices carried out on the manufacturing farms was collected through a checklist, from which interventions were proposed to improve these practices. In all visits, samples of milk from the tank, and a sample of cheese were collected. The results of analyzes of the centesimal composition of the milk showed that there was a statistical difference between the three farms for all analyzed variables (p0.05), except for the urea content (p0.05). The values of Standard Plate Count and Somatic Cell Count were in accordance with the current health legislation in farms B and C. The cheese from farm A had higher levels of fat and total solids, while the cheese from farm C had higher levels of protein and lactose. The results of the microbiological analyzes of the cheese samples showed a statistical difference between the three farms regarding the presence of coliforms at 35°C (p0.05), with the lowest value in farm A. The counts of coliforms at 45°C and Staphylococcus spp. showed no statistical difference and all collected samples showed the absence of Listeria spp. and Salmonella spp. It was verified that a ripening period of only 15 days was not enough for the cheeses to present values within the established parameters for Staphylococcus spp.